2019
DOI: 10.1088/1742-6596/1293/1/012064
|View full text |Cite
|
Sign up to set email alerts
|

Numerical simulation of the fast processes in HTS tapes under the pulsed current load

Abstract: This paper presents a numerical layered 2G HTS tape model with the transport current flowing through it. The simulation is performed by using FEM H-formulation method implemented in the Comsol Multyphysics software. The model provides two cooling modes: cryocooler and liquid nitrogen. LN2 cooling mode provides for a complex hysteresis character of the liquid nitrogen boiling curve and the boiling regimes changing possibility between the stationary and the bubble boiling. The delay of the voltage rising with a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
2
0
3

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 5 publications
0
2
0
3
Order By: Relevance
“…32), as well as the calculation of the vertical force based on the levitation gap for loop-type configuration (Fig. 33 Either single permanent magnets or their assemblies in the form of co-oriented magnets [166,167], oppositeoriented magnets [148,168], as well as Halbach assembly [169,170] are the most frequently used in levitation systems. Comparison of the levitation force for HTS-belt stacks in the fields of different magnetic assemblies is given in the work [169].…”
Section: Some Of the Results Of Calculation Models Applicationmentioning
confidence: 99%
See 1 more Smart Citation
“…32), as well as the calculation of the vertical force based on the levitation gap for loop-type configuration (Fig. 33 Either single permanent magnets or their assemblies in the form of co-oriented magnets [166,167], oppositeoriented magnets [148,168], as well as Halbach assembly [169,170] are the most frequently used in levitation systems. Comparison of the levitation force for HTS-belt stacks in the fields of different magnetic assemblies is given in the work [169].…”
Section: Some Of the Results Of Calculation Models Applicationmentioning
confidence: 99%
“…33 Either single permanent magnets or their assemblies in the form of co-oriented magnets [166,167], oppositeoriented magnets [148,168], as well as Halbach assembly [169,170] are the most frequently used in levitation systems. Comparison of the levitation force for HTS-belt stacks in the fields of different magnetic assemblies is given in the work [169]. It is shown that for using in transport systems, where it is required to maintain relatively high levitation gap, the use of opposite-oriented magnet assembly is more beneficial, meanwhile in the systems, where a priority parameter is the value of the levitation force, the use of Halbach magnet assembly is beneficial, because this provides a high interaction force, which, however, falls rapidly by height (Fig.…”
Section: Some Of the Results Of Calculation Models Applicationmentioning
confidence: 99%
“…32), а также расчет вертикальной силы от левитационного зазора для петлевой конфигурации (рис. 33) В левитационных системах наиболее часто используются либо одиночные постоянные магниты, либо их сборки в виде сонаправленных магнитов [166,167], встречно-ориентированных магнитов [148,168], а также сборкой Халбаха [169,170]. Сравнение левитационной силы для стопок ВТСП-лент в полях различных магнитных сборок приведено в работе [169].…”
Section: некоторые результаты применения расчетных моделейunclassified
“…33) В левитационных системах наиболее часто используются либо одиночные постоянные магниты, либо их сборки в виде сонаправленных магнитов [166,167], встречно-ориентированных магнитов [148,168], а также сборкой Халбаха [169,170]. Сравнение левитационной силы для стопок ВТСП-лент в полях различных магнитных сборок приведено в работе [169]. Показано, что для использования в танспортных системах, где необходимо соблюдать относительно большой левитационный зазор, наиболее выгодно использовать магнитную сборку со встречно-ориентированными магнитами, тогда как в системах, в которых приоритетным параметром является величина левитационной силы, выгодно использовать магнитную сборку Халбаха, поскольку данная сборка обеспечивает высокую силу взаимодействия, однако эта сила быстро убывает с высотой (рис.…”
Section: некоторые результаты применения расчетных моделейunclassified
“…В работе [17] систематически исследовались магнитные свойства стопки ВТСП-лент, получены кривые намагниченности при различной температуре и числе лент N в стопке, измерена сила левитации. Подробнее аналогичные данные получены также для отдельных ВТСП-лент и стопок ВТСП-лент, представляющих собой наборную конструкцию с многочисленными слоями ВТСП [18][19][20][21]. Показано, что величина остаточной намагниченности выходит на насыщение, а скорость релаксации остаточной намагниченности падает при увеличении N. В серии работ [22,23] разработан метод для расчета кривых намагниченности и силы левитации сверхпроводника второго рода, помещенного в однородное и неоднородное магнитное поле.…”
Section: Introductionunclassified